Respuesta :
Question 1:
Given the three zeros
[tex]x = 4[/tex]
[tex]x = -14[/tex]
[tex]x = 5+8i[/tex]
The other zero will be the conjugate pair of [tex]5+8i[/tex]
[tex]x = 5-8i[/tex]
Writing these zeros in factorized form of f(x) gives:
[tex](x-4)(x+14)(x-(5+8i))(x-(5-8i))[/tex] → Multipy out the first two brackets to get
[tex](x^2+10x-56)(x-5-8i)(x-5+8i)[/tex]
[tex](x^2+10x-56)(x^2-5x+8ix-5x+25-40i-8ix+40i-64i^2)[/tex]
[tex](x^2+10x-56)(x^2-10x+25-64(-1))[/tex]
[tex](x^2+10x-56)(x^2-10x+25+64)[/tex]
[tex](x^2+10x-56)(x^2-10x+89)[/tex]→ Multiply out further
[tex]x^4-10x^3+89x^2+10x^3-100x^2+890x-56x^2+560x-4984[/tex]
[tex]x^4+89x^2-100x^2-56x^2+1450x-4984[/tex]
[tex]x^4-67x^2+1450x-4984[/tex]
Answer: C
-------------------------------------------------------------------------------------------------------------
Question 2
Given [tex]x^5+7x^4+2x^3+14x^2+x+7[/tex]
Collecting two terms together to get
[tex](x^5+7x^4)+(2x^3+14x^2)+(x+7)[/tex]
[tex][x^4(x+7)]+[2x^2(x+7)]+[x+7][/tex]
Notice that each group has common factor [tex](x+7)[/tex]
Factorise the common factor gives
[tex](x+7)[x^4+2x^2+1][/tex]
[tex](x+7)(x^2+1)(x^2+1)[/tex]
The zeros are
[tex]x+7 = 0[/tex] and four of [tex]x^2+1=0[/tex]
The zero [tex]x^2+1=0[/tex] will give an imaginary results
So, f(x) has one real root and four imaginary root
Answer: B
---------------------------------------------------------------------------------------------------------------
Question 3
[tex]f(x) = x^4+16x^2[/tex]
[tex]f(x) = x^2(x^2+16)[/tex]
The zeros are
[tex]x^2=0[/tex] and [tex]x^2+16=0[/tex]
[tex]x_{1,2} = 0[/tex] and [tex]x_{3, 4} = \sqrt{-16} [/tex]
[tex] \sqrt{-16}= \sqrt{16} \sqrt{-1} [/tex] which gives two answers: [tex]4i[/tex] and [tex]-4i[/tex]
So the factorized form is
[tex]x^2(x+4i)(x-4i)[/tex]
Answer: C
----------------------------------------------------------------------------------------------------------------
Question 4
If [tex]i[/tex] is one of the zeros of [tex]f(x)[/tex] then the other zero would be to conjugate pair of [tex]i[/tex] which is [tex]-i[/tex]
Answer: B
-----------------------------------------------------------------------------------------------------------
Question 5
[tex]f(x) = \frac{7}{14-x} [/tex]
The denominator must not equal zero because we can't divide a quantity by zero (undefined result)
So, we need to find the value of [tex]x[/tex] that would make the denominator equal to zero
[tex]14 - x = 0[/tex]
[tex]x = 14[/tex]
Answer: A
-------------------------------------------------------------------------------------------------------------
Question 6
[tex]f(x) = \frac{(x-7)(x+4)}{(x^2-4)} [/tex]
To find vertical asymptote, set the denominator to zero then find 'x'
[tex]x^2-4=0[/tex]
[tex]x^2 = 4[/tex]
[tex]x = 2[/tex] and [tex]x = -2[/tex]
Answer: A
----------------------------------------------------------------------------------------------------------
Question 7
[tex]f(x) = \frac{x+9}{x^2+8x+5} [/tex]
The degree of the denominator is higher than the numerator's, hence the horizontal asymptote is y = 0
------------------------------------------------------------------------------------------------------------
Question 8
[tex]f(x) = \frac{x^2+9x-9}{x-9} [/tex]
The degree of numerator is higher than the degree of the denominator, hence no horizontal asymptote
------------------------------------------------------------------------------------------------------------
Question 9
To have a horizontal asymptote, [tex]y = \frac{2}{9} [/tex], both numerator and denominator must be on the same polynomial degree, and the leading degree have coefficient of 2 and 9
Example: [tex] \frac{2x^2+3x+6}{9x^2+6x+9} [/tex]
Given the three zeros
[tex]x = 4[/tex]
[tex]x = -14[/tex]
[tex]x = 5+8i[/tex]
The other zero will be the conjugate pair of [tex]5+8i[/tex]
[tex]x = 5-8i[/tex]
Writing these zeros in factorized form of f(x) gives:
[tex](x-4)(x+14)(x-(5+8i))(x-(5-8i))[/tex] → Multipy out the first two brackets to get
[tex](x^2+10x-56)(x-5-8i)(x-5+8i)[/tex]
[tex](x^2+10x-56)(x^2-5x+8ix-5x+25-40i-8ix+40i-64i^2)[/tex]
[tex](x^2+10x-56)(x^2-10x+25-64(-1))[/tex]
[tex](x^2+10x-56)(x^2-10x+25+64)[/tex]
[tex](x^2+10x-56)(x^2-10x+89)[/tex]→ Multiply out further
[tex]x^4-10x^3+89x^2+10x^3-100x^2+890x-56x^2+560x-4984[/tex]
[tex]x^4+89x^2-100x^2-56x^2+1450x-4984[/tex]
[tex]x^4-67x^2+1450x-4984[/tex]
Answer: C
-------------------------------------------------------------------------------------------------------------
Question 2
Given [tex]x^5+7x^4+2x^3+14x^2+x+7[/tex]
Collecting two terms together to get
[tex](x^5+7x^4)+(2x^3+14x^2)+(x+7)[/tex]
[tex][x^4(x+7)]+[2x^2(x+7)]+[x+7][/tex]
Notice that each group has common factor [tex](x+7)[/tex]
Factorise the common factor gives
[tex](x+7)[x^4+2x^2+1][/tex]
[tex](x+7)(x^2+1)(x^2+1)[/tex]
The zeros are
[tex]x+7 = 0[/tex] and four of [tex]x^2+1=0[/tex]
The zero [tex]x^2+1=0[/tex] will give an imaginary results
So, f(x) has one real root and four imaginary root
Answer: B
---------------------------------------------------------------------------------------------------------------
Question 3
[tex]f(x) = x^4+16x^2[/tex]
[tex]f(x) = x^2(x^2+16)[/tex]
The zeros are
[tex]x^2=0[/tex] and [tex]x^2+16=0[/tex]
[tex]x_{1,2} = 0[/tex] and [tex]x_{3, 4} = \sqrt{-16} [/tex]
[tex] \sqrt{-16}= \sqrt{16} \sqrt{-1} [/tex] which gives two answers: [tex]4i[/tex] and [tex]-4i[/tex]
So the factorized form is
[tex]x^2(x+4i)(x-4i)[/tex]
Answer: C
----------------------------------------------------------------------------------------------------------------
Question 4
If [tex]i[/tex] is one of the zeros of [tex]f(x)[/tex] then the other zero would be to conjugate pair of [tex]i[/tex] which is [tex]-i[/tex]
Answer: B
-----------------------------------------------------------------------------------------------------------
Question 5
[tex]f(x) = \frac{7}{14-x} [/tex]
The denominator must not equal zero because we can't divide a quantity by zero (undefined result)
So, we need to find the value of [tex]x[/tex] that would make the denominator equal to zero
[tex]14 - x = 0[/tex]
[tex]x = 14[/tex]
Answer: A
-------------------------------------------------------------------------------------------------------------
Question 6
[tex]f(x) = \frac{(x-7)(x+4)}{(x^2-4)} [/tex]
To find vertical asymptote, set the denominator to zero then find 'x'
[tex]x^2-4=0[/tex]
[tex]x^2 = 4[/tex]
[tex]x = 2[/tex] and [tex]x = -2[/tex]
Answer: A
----------------------------------------------------------------------------------------------------------
Question 7
[tex]f(x) = \frac{x+9}{x^2+8x+5} [/tex]
The degree of the denominator is higher than the numerator's, hence the horizontal asymptote is y = 0
------------------------------------------------------------------------------------------------------------
Question 8
[tex]f(x) = \frac{x^2+9x-9}{x-9} [/tex]
The degree of numerator is higher than the degree of the denominator, hence no horizontal asymptote
------------------------------------------------------------------------------------------------------------
Question 9
To have a horizontal asymptote, [tex]y = \frac{2}{9} [/tex], both numerator and denominator must be on the same polynomial degree, and the leading degree have coefficient of 2 and 9
Example: [tex] \frac{2x^2+3x+6}{9x^2+6x+9} [/tex]